Computational assessment of the effects of pre-chamber and piston geometries on the combustion characteristics of an optical pre-chamber engine. (1st June 2023) - Liu, Xinlei; Echeverri Marquez, Manuel; Sanal, Sangeeth; Silva, Mickael; AlRamadan, Abdullah S.; Cenker, Emre; Sharma, Priybrat; Magnotti, Gaetano; Turner, James W.G.; Im, Hong G.
Highlights: Abundant OH was generated from reacting jets downstream of the nozzle exits. PC with smaller nozzles generated more reacting jets due to severe gas choke. A large PC led to an intense pressure buildup owing to the more trapped fuel. The flat piston led to earlier flame-wall interaction and higher heat transfer loss. MC combustion phasing was not significantly sensitive to jet flame features. Abstract: Pre-chamber combustion (PCC) has the potential to extend the lean-burn limit in spark-ignition engines, which can promote engine efficiency and relieve the concern of emissions of nitrogen oxides. This work assessed the effects of pre-chamber (PC) and piston geometries on the combustion characteristics of an optical methane PCC engine with both experimental and computational approaches. Five active-type PCs with different volumes and nozzle diameters (12 nozzles distributed evenly in two layers) and two pistons (bowl and flat) were tested under lean-burn conditions. Multi-cycle pressure and heat release profiles, natural flame luminosity images, and OH* chemiluminescence images were measured and employed for CFD modeling validations. The PCs with the smaller nozzle diameter yielded more intensely-reacting jets from the upper layer of nozzles compared to the other PCs, attributed to the stronger gas choke there, which dramatically affected the flow fields. A larger PC volume allowed more air–fuel mixture to be trapped within the PC whose combustion then resulted in faster pressure buildup, which, however, led to higher heat transfer loss. Compared to the bowl piston, the flat piston generated a higher heat release rate during the late combustion period owing to the relatively longer jet propagation within the squish region.